Comparison of conventional pulmonary rehabilitation and high‐frequency chest wall oscillation in primary ciliary dyskinesia. Issue 6 (30th August 2013) - Gokdemir, Yasemin; Karadag‐Saygi, Evrim; Erdem, Ela; Bayindir, Ozun; Ersu, Refika; Karadag, Bulent; Sekban, Nimet; Akyuz, Gulseren; Karakoc, Fazilet
Summary Background Enhancement of mucociliary clearance by pulmonary rehabilitation (PR) is advocated in primary ciliary dyskinesia (PCD). Our primary aim was to compare the efficacy and safety of postural drainage, percussion and vibration [conventional PR (CPR)], and high frequency chest wall oscillation (HFCWO) by studying change in pulmonary function. Our secondary aim was to evaluate patient preferences regarding the two methods. Methods This was a controlled randomized crossover study. PCD patients between the ages of 7 and 18 years were assigned to two groups, first group performed airway clearance with CPR at hospital for 5 days and after a 2‐day washout period HFCWO was applied to the same group at home. HFCWO was applied first to the other group and then these patients were hospitalized for CPR. The primary outcome measure of the study was pulmonary function test (PFT). The secondary outcomes were pulse arterial oxygen saturation (SpO2) and the perceived efficiency and comfort level. Results PFT values of patients increased significantly after both PR methods (before/after): CPR: FVC: 77.0 ± 14.1/81.8 ± 13.0 (P = 0.002); FEV1: 72.9 ± 14.8/78.7 ± 13.5 (P = 0.001); PEF: 73.8 ± 14.5/82.5 ± 14.5 (P = 0.001); FEF25–75: 68.6 ± 27.6/74.9 ± 29.3 (P = 0.007). HFCWO: FVC: 75.1 ± 15.3/80.3 ± 13.9 (P = 0.002); FEV1: 71.4 ± 16/77.4 ± 14.6 (P = 0.001); PEF: 70.9 ± 18.0/78.3 ± 17.7 (P = 0.002); FEF25–75: 70.5 ± 23.4/76.4 ± 25.6 (P = 0.006). There were no significant differences in % predicted FVC, FEV1, PEF, and FEF25–75 increased values with CPR and HFCWO. HFCWO was found more comfortable (P = 0.04). Two PR methods were found efficient and no desaturation occurred during PR. Conclusions PFTs were significantly increased after both PR methods. There were no differences in PFTs and SpO2 between the CPR and HFCWO groups. Both PR methods were found efficient. HFCWO was found more comfortable. HFCWO may be an option in patients with chronic pulmonary disease and low adherence to PR. Pediatr Pulmonol. 2014; 49:611–616. © 2013 Wiley Periodicals, Inc.